An analysis of market power and efficiency of Islamic banking in Indonesia and Malaysia - Chajar Matari Fath Mala; M Nadratuzzaman Hosen; M Nur Rianto Al Arif (Jurnal Ekonomi & Keuangan Islam, 2023)
Purpose – This paper aims to investigate whether the Islamic banking industry in Indonesia and Malaysia is collusive or efficient. Indonesian Islamic banking is expected to meet the Qualified ASEAN Bank (QAB) to compete with other Islamic banks, including Malaysia.Methodology – The data used in this study was panel data on Islamic banking in Indonesia and Malaysia from January 2010 to December 2019. Data analysis employed static panel data regression.Findings – The findings of the study disclosed no collusive behavior from Islamic banking in Indonesia and Malaysia to increase profitability. Meanwhile, market share has been shown to boost profitability in terms of equity, despite the fact that there is an endogeneity problem. Technical efficiency and scale efficiency in Islamic banking in Indonesia have been shown to significantly increase market share, but not profitability and market power. This study concludes that if Islamic banking market in Indonesia and Malaysia are opened and state boundaries are lifted, Indonesian Islamic banking still will not be able to compete since it has not been able to acquire economies of scale.Implications – Islamic banking in Indonedia needs to establish Islamic-Finance-Friendly Regulations. It is expected to pave the way for the value-added character of Islamic banking, it is the most important strategy to boost market share of Indonesian Islamic banking.Originality – This study seeks to fill the validation gap of endogeneity test in Islamic banking. There is the limitation on studies of Islamic banks since the validation of endogeneity test deal only with conventional banking studies.